2015
DOI: 10.1111/ans.13409
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous bile leak

Abstract: Fig. 3. Endoscopic retrograde cholangiopancreatography demonstrating leak from a segment IVb subsegmental duct. 2Images for surgeons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, a large body of research defines bile leak as a broader term. Using the PubMed search function, a significant amount of literature was found that referred to "spontaneous bile leak," a term used to refer to a leakage of biliary fluid that did not follow surgical intervention of any kind [4,[9][10][11][12][13]. Spontaneous bile leak has been defined as a bile leak "where a specific cause remains unidentifiable and is usually a diagnosis of exclusion" [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, a large body of research defines bile leak as a broader term. Using the PubMed search function, a significant amount of literature was found that referred to "spontaneous bile leak," a term used to refer to a leakage of biliary fluid that did not follow surgical intervention of any kind [4,[9][10][11][12][13]. Spontaneous bile leak has been defined as a bile leak "where a specific cause remains unidentifiable and is usually a diagnosis of exclusion" [9].…”
Section: Discussionmentioning
confidence: 99%